Exome sequencing analysis of gastric primary myeloid sarcoma with monocytic differentiation with altered immunophenotype after chemotherapy: case report - Xiang Li; Hongxia Zhang; Yong Cui; Haijun Zhang; Yonggang Wang; Meili Ding; Xingyao Zhu; Ruiqi Zhang; Qi Hu; Lin Tao; Wenhao Hu; Xinxia Li; et al. (BMC, 2023)
Highlights 1. We used exome sequencing to detect and report the genetic changes in a case of extramedullary gastric primary myeloid sarcom with monocytic differentiationa. 2. Immunophenotypic alteration of tumor cells occurred after chemotherapy, suggesting that chemotherapy drugs induced tumor differentiation.